Outstanding Primary Leadership in Times of Turbulence - Colin Howard (MDPI AG, 2021)
Leadership and management in schools have sought to produce high quality education for all pupils. To inform and support school leaders’ educationalists have developed theories and undertaken research studies identifying the relationships, contexts and characteristics that enable effective leadership. However, recent times of turbulence in primary schools have had an inevitable impact upon the key drivers for successful leadership and management. This study builds upon our previous research into outstanding leadership in primary education to examine the impact that such change has had upon the leadership of serving head teachers. It utilises an adapted Q-sort methodology to identify the views of serving head teachers to gain insights into the impact that such change has had upon their leadership. Overall, the analysis identified a need for aspirational characteristics of leadership, underpinned by personal values to guide schools in such times, as they strive to produce high quality education.